2014
DOI: 10.3851/imp2925
|View full text |Cite
|
Sign up to set email alerts
|

Baseline CD4+ T-cell Count and Cardiovascular Risk Factors Predict the Evolution of Cognitive Performance During 2-Year follow-up in HIV-Infected Patients

Abstract: Immunological parameters and cardiovascular risk factors are independently associated with the evolution of cognitive status in HIV+ patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…Only one of 31 studies reviewed herein tested the visuospatial sketchpad of patients with HIV infection . The authors observed similar performances in the spatial span (forward) task of patients at baseline [mean score 4.09 (SD 0.9)] and after 2 years [mean score 5.2 (SD 0.8)] ( P = 0.001), but, again, conclusions are hampered by the absence of healthy controls.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Only one of 31 studies reviewed herein tested the visuospatial sketchpad of patients with HIV infection . The authors observed similar performances in the spatial span (forward) task of patients at baseline [mean score 4.09 (SD 0.9)] and after 2 years [mean score 5.2 (SD 0.8)] ( P = 0.001), but, again, conclusions are hampered by the absence of healthy controls.…”
Section: Resultsmentioning
confidence: 85%
“…In the data set analysed in this study, nadir CD4 counts were reported in 13 of 31 studies . In a sample of patients whose average nadir CD4 count was 214 (interquartile range 100–305) cells/μL, episodic memory impairment was not detected, but impaired psychomotor speed and motor function were found in association with a slightly smaller thalamus and total brain volume .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…51 In two 2-year cohorts from Italy and France with 95% ART coverage, the prevalence of NCI was very similar both at baseline and at study completion. 52,53 An earlier US cohort study, enrolled between 2001 and 2005, found declining cognitive function in 35% of the 215 patients followed up (of 276 originally enrolled), but there was a 56% prevalence of "substance abuse or dependence", and treatment and adherence may have been suboptimal by current standards. 54 Other classic screening criteria are that the natural history of a condition, including its development from silent to clinical disease, should be well-understood, and there should be a recognizable latent or early symptomatic stage.…”
Section: Outcomes and Impacts Of Hiv-associated Nci In Treated Patientsmentioning
confidence: 99%
“…With advancing age, individual presenting HAND are at greater for progressive deterioration of daily life activities, medical decisionmaking and quality-of-life [14][15][16]. In a study deriving an estimate of 'cognitive reserve from the Brief Intelligence Test and the Cognitive Reserve Index, it was observed that lifestyle choices affected copingcapacity to deal with HIV in aging and HIV-related neurodegeneration [17,18]. It has been shown that in a cohort of HIV patients (aged 60 years and above) that the adherence to antiretroviral therapy was related to cognitive impairment [12], apolipoprotein E4 genotype, monocyte efficacy scores, with trend associations for diabetes and low CD4+ cell count [19,20].…”
mentioning
confidence: 99%